2019
DOI: 10.1660/062.122.0309
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary PCR-Based Screening Indicates a Higher Incidence of Porcine Endogenous Retrovirus Subtype C (PERV-C) in Feral Versus Domestic Swine

Abstract: Xenotransplantation is considered a potential alternative to allotransplantation to relieve the current shortage of human organs. Due to their similar size and physiology, the organs of pigs are of particular interest for this purpose. Endogenous retroviruses are a result of integration of retroviral genomes into the genome of infected germ cells as DNA proviruses, which are then carried in all cells of the offspring of the organism. Porcine endogenous retroviruses (PERVs) are of special concern because they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Retroviral genomes become integrated into the genome of infected germ cells and thus they are detected in organs and tissues, which can be used for xenotransplantation (Acharya et al, 2019). This genus included mainly Porcine-type-C oncovirus species and cause malignant disease in animals and humans as shown in vitro by Acharya et al (2019); similarly Kim et al (2016) reported that viral zoonosis occurred under particular host conditions, such as immunosuppressive treatment and transplantation with hostadapted virus-producing cells, and thus transmission of PERV was created from different recipient cells in vivo. However, the in-vivo studies by Denner (2018) showed that PERV transmission has not been observed in any of the many preclinical and clinical xenotransplantation trials performed so far, and not in any of the many experimental PERV-infection experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral genomes become integrated into the genome of infected germ cells and thus they are detected in organs and tissues, which can be used for xenotransplantation (Acharya et al, 2019). This genus included mainly Porcine-type-C oncovirus species and cause malignant disease in animals and humans as shown in vitro by Acharya et al (2019); similarly Kim et al (2016) reported that viral zoonosis occurred under particular host conditions, such as immunosuppressive treatment and transplantation with hostadapted virus-producing cells, and thus transmission of PERV was created from different recipient cells in vivo. However, the in-vivo studies by Denner (2018) showed that PERV transmission has not been observed in any of the many preclinical and clinical xenotransplantation trials performed so far, and not in any of the many experimental PERV-infection experiments.…”
Section: Discussionmentioning
confidence: 99%